ANALISIS KEPATUHAN TAX PAYER ALAT ANGKUT BERMOTOR - Ningrum, Rani Ulan; Linawati, Linawati; Zaman, Badrus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Banyakan District, Kediri Regency is one of the areas that has used and implemented the e-Samsat program and for 10 years the program has been running. The local government has also been following technological developments that continue to increase so that they can optimally utilize technology to support taxpayer awareness in paying their PKB. To analyze and determine the effect of the modernization of the e-Samsat system, the level of income, and partial and simultaneous tax sanctions on the compliance of motorized vehicle taxpayers is the goal to be achieved in this study. Quantitative is the approach, causal is the technique. Questionnaire is a data collection tool. All motorized vehicle taxpayers in the Banyakan sub-district are the population. 40 respondents are the sample. Accidental sampling is a sampling technique. Multiple linear regression analysis is the analytical tool. The conclusion of this study is that the modernization of e-samsat, income levels, and tax sanctions have a significant partial and simultaneous effect on compliance with motorized vehicle taxpayers. Assessing income levels during covid is the novelty of this research.